The existentialist renunciation of romantic dream of infinitude in the Hobbesian State of Nature - Ríos Álvarez, Clara (Pensamiento. Revista de Investigación e Información Filosófica, 2016)
Beyond the devastating anthropology derived from Hobbes’s works, the dichotomy vainglory-fear of death allows for shedding some light on Hobbesian philosophy making use of Hegel’s master-slave dialectic as a hermeneutic key. This different view provides us with a new metaphysical and existentialist perspective to reinterpret Hobbesian politics as an almost philanthropic humanism. As a result, power relationships occurred in the state of nature could be considered as an unavoidable fight of human being against himself to reach society. Political space becomes an essential condition for humanity, and not just for survival, the triumph of sanity over passionate desire for infinitude. This article tries to suggest an alternative interpretation of Hobbes’s contractualism in accordance with the overwhelming preciseness of his thinking. At the same time, this pruritus might allow us to dignify the historical image of an author whose influences can be found in the most important leading figures of Modernity and Contemporaneity.